2009
DOI: 10.1111/j.1477-2574.2009.00094.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of pre-operative serum creatinine on short-term outcomes after liver resection

Abstract: After liver resection, renal failure is rare but patients with an elevated creatinine pre-operatively are at an increased risk of both renal and non-renal complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 18 publications
2
21
1
Order By: Relevance
“…Despite the differences in age and comorbidity, this study showed no difference in the rate of surgical complications between the two groups. Systemic complications accounted for the higher rates of postoperative morbidity in patients with elevated serum creatinine 27. In our study, creatinine was not significantly associated with posthemihepatectomy complications and also the grade of complication.…”
Section: Discussioncontrasting
confidence: 57%
“…Despite the differences in age and comorbidity, this study showed no difference in the rate of surgical complications between the two groups. Systemic complications accounted for the higher rates of postoperative morbidity in patients with elevated serum creatinine 27. In our study, creatinine was not significantly associated with posthemihepatectomy complications and also the grade of complication.…”
Section: Discussioncontrasting
confidence: 57%
“…The effect of hepatic function on renal function is well known and of particular interest in patients with acute or chronic liver failure20. The impact of a raised preoperative serum creatinine level on postoperative renal function and non‐renal complications is well known21. The present evaluation of serum creatinine and urea levels in patients who had an uncomplicated hepatectomy revealed very constant levels of both parameters, with little fluctuation depending on the extent of resection.…”
Section: Discussionmentioning
confidence: 60%
“…Short-term outcomes of patients in this series are similar to those reported by other authors. [7][8][9][11][12][13][14][15][16]20 In one of the previous studies based on an unselected series of 1005 liver resections performed in the Department of General, Transplant and Liver Surgery at the Medical University of Warsaw, overall morbidity and mortality rates were 22.1% and 1.4%, respectively. 19 Although several studies have reported zero or near-zero mortality after a liver resection, most of these report only in-hospital or 30-day rates.…”
Section: Discussionmentioning
confidence: 99%